2017
DOI: 10.1002/jbm.a.36135
|View full text |Cite
|
Sign up to set email alerts
|

G‐CSF loaded nanofiber/nanoparticle composite coated with collagen promotes wound healing in vivo

Abstract: Sustained release of functional growth factors can be considered as a beneficial methodology for wound healing. In this study, recombinant human granulocyte colony-stimulating factor (G-CSF)-loaded chitosan nanoparticles were incorporated in Poly(ε-caprolactone) (PCL) nanofibers, followed by surface coating with collagen type I. Physical and mechanical properties of the PCL nanofibers containing G-CSF loaded chitosan nanoparticles PCL/NP(G-CSF) and in vivo performance for wound healing were investigated. G-CSF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…Loading efficiency of GM-CSF was as high as 97.4 ± 1.68% with sustained release of~100% over 48 h and in vivo experiments have shown that composites loaded with encapsulated GM-CSF in CS NPs induce greater wound closure compared to the composite alone [50]. Polycaprolactone nanofibers loaded with CS NPs containing GM-CSF also showed accelerated wound closure [51]. Modification of CS with peptides also promotes wound closure, for example, CS hydrogels made from Ser-Ile-Lys-Val-Ala-Val-chitosan macromers [52] when applied in vivo induces collagen expression, angiogenesis, expression of TGF-β1, and inhibits the expression of TNF-α, IL-1β, and IL-6 mRNA in a mouse skin wound model [53].…”
Section: Chitosan For Wound Healingmentioning
confidence: 99%
“…Loading efficiency of GM-CSF was as high as 97.4 ± 1.68% with sustained release of~100% over 48 h and in vivo experiments have shown that composites loaded with encapsulated GM-CSF in CS NPs induce greater wound closure compared to the composite alone [50]. Polycaprolactone nanofibers loaded with CS NPs containing GM-CSF also showed accelerated wound closure [51]. Modification of CS with peptides also promotes wound closure, for example, CS hydrogels made from Ser-Ile-Lys-Val-Ala-Val-chitosan macromers [52] when applied in vivo induces collagen expression, angiogenesis, expression of TGF-β1, and inhibits the expression of TNF-α, IL-1β, and IL-6 mRNA in a mouse skin wound model [53].…”
Section: Chitosan For Wound Healingmentioning
confidence: 99%
“…Moreover, to increase cell attachment, the scaffold was coated with collagen I. In vivo experiments demonstrated improved wound closure, scar reduction, fibroblasts maturation, as well as increased collagen density and a decreased amount of neutrophils (Tanha et al, 2017).…”
Section: Nanoparticlesmentioning
confidence: 99%
“…This morphology of nanofibers can be employed to repair skin tissue in wound healing, as the ECM fibers of skin are also unaligned. For example, isotropic PCL nanofibers have been used to adsorb chitosan nanoparticles containing human granulocyte colony stimulating factor (G-CSF) for skin tissue regeneration [111]. Additionally, heparin mimetic peptide nanofibers with unaligned morphology dramatically promoted the tissue regeneration of burn injury [112].…”
Section: Fiber Orientationmentioning
confidence: 99%